2022
DOI: 10.1002/jssc.202200028
|View full text |Cite
|
Sign up to set email alerts
|

A novel three‐dimensional printed device with conductive elements for electromembrane extraction combined with high‐performance liquid chromatography and ultraviolet detector

Abstract: This study is focused on proposing a new design and setup for electromembrane extraction. A new cap was designed and conductive vials of different shapes were fabricated using three‐dimensional printing. The new cap holds three fibers to enhance electromembrane extraction recovery. Conductive vials can simultaneously perform as electrodes therefore, there is no need to include an electrode in sample solutions. Phenobarbital and phenytoin were used as model compounds to assess the setup performance. Under optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Furthermore, the proposed method was compared with some other available methods based on MIPs or membrane extraction in the literature for PHT, PHB, and/or LTG. 28–33,47–53 As shown in Table 6, the extraction recovery of the current method for PHT in plasma was similar with that in the works by Jia's group 28 and Yaripour's group 33 but higher than that in other methods. 47,48,53 The extraction recovery of the current work for PHT in aqueous solution was obviously higher than that in the reference methods.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Furthermore, the proposed method was compared with some other available methods based on MIPs or membrane extraction in the literature for PHT, PHB, and/or LTG. 28–33,47–53 As shown in Table 6, the extraction recovery of the current method for PHT in plasma was similar with that in the works by Jia's group 28 and Yaripour's group 33 but higher than that in other methods. 47,48,53 The extraction recovery of the current work for PHT in aqueous solution was obviously higher than that in the reference methods.…”
Section: Resultssupporting
confidence: 80%
“…47,48,53 The extraction recovery of the current work for PHT in aqueous solution was obviously higher than that in the reference methods. 47,52 In the case of PHB, the extraction recovery in the current work for plasma was higher than that of the reported methods, 50,53 while the extraction recovery in current work for aqueous solution was higher than that of MIPs or electromembrane extraction 49,52,53 but similar with that of MIP fiber extraction, 29 which may result from the similar characters between MIP fiber and MIPMs. In the case of LTG, the extraction recovery of the employed method for plasma or aqueous solution was lower than that of previous works based on MIPs, 30–32,51 which may result from the different templates used to prepare the MIPs.…”
Section: Resultsmentioning
confidence: 61%
“…The transition of EME from research to a broadly applicable microextraction technique necessitates standardized and commercial equipment and the development of generic methods. Three-dimensionally-printed devices have been developed recently and address standardization [9]. Furthermore, commercial EME equipment has recently emerged [10], with vials designed for samples and acceptors composed of conductive polymer.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the researchers found that the actuate membrane materials including sodium alginate [8] , cellulose, chitosan [9][10][11][12] . Due to their unique three-dimensional network structure and ability to retain a large amount of water, ion actuator had a wide range of applications in hydrogel arti cial muscles [13] including biomedical applications, drug carriers [14][15] , biosensors [16] , medical devices [17] , tissue engineering [18] , separation systems [19][20] , micro uidic systems [21] , microvalves [22] and actuator [23][24] . Chitosan (CS) was a product of natural chitin.…”
Section: Introductionmentioning
confidence: 99%